Determinants of the Extent of Voluntary Disclosure in the Annual Reports of the Tunisian Firms - Raida Chakroun; Hamadi Matoussi (Journal of Accounting and Management Information Systems (JAMIS), 2012)
The main purpose of this paper is to analyze the interactions between the external and internal mechanisms of governance and voluntary disclosure in the annual reports (external mechanism of governance) in the Tunisian emerging market. Our investigation is specifically about the study of the direct links between the regulatory reform, competition on the market of goods and services, ownership structure, composition of the board of directors, and the extents of voluntary disclosure in the annual reports either closely linked to mandatory disclosure or not. We conducted our statistical analysis on a sample of Tunisian listed firms of the non-financial sector of 144 observations (firm-years) during the period 2003-2008. The results of this study show that the firms of our sample tend to disclose voluntary information closely linked to mandatory disclosure rather the one not closely linked. Moreover, the results provide a strong support that both indexes of voluntary disclosure (closely linked to mandatory disclosure and the one not closely linked) are affected by the external and internal mechanisms of governance. Specifically, governance mechanisms sometimes represent substitutes and sometimes complements to both measures of the voluntary disclosure extents. Nevertheless, we find that the impacts of the institutional and managerial ownership on the extent of both the voluntary disclosure not closely linked to mandatory disclosure and the one closely linked are similar. However, the effects of the other variables are different either in significance, in sign, or in magnitude.
Keywords: M41; M48; 650; Voluntary disclosure; mandatory disclosure; annual reports; external mechanisms of governance; internal mechanisms of governance